The Problem of Chronic Oxidative Stress and the Systemic Indirect Ozone Therapy as a Possible Solution - Emma Borrelli (Highlights on Medicine and Medical Research Vol. 4, 2021)
A large series of studies reported that unhealthy lifestyle, such as high fat, heavily salted diet, reduced physical activity and tobacco smoking is a direct or indirect cause of cardiovascular diseases, chronic respiratory diseases, diabetes and neurodegenerative diseases. In all these diseases the main cause of death is a remarkable increase of circulating reactive oxygen species (ROS), proinflammatory cytokines and acute-phase proteins. Consequently, bedsides promoving healthier diets and reducing the use of alcohol and tobacco, it appears indispensable to correct the chronic oxidative stress during the development of the chronic pathology. Thus, the official orthodox treatments of anti-hypertensive, anti-cholesterolemic and antidiabetics drugs need to be integrate with a modulator able to re-establish the oxidant/antioxidant balance in the cells. It has been demonstrated that the judicious application of ozone in the atrophic form of ARMD, chronic vasculopathies, Type II diabetes, chronic obstructive pulmonary disease (COPD), wound healing disorders, orthopedics and dentistry produce a positive biochemical and clinical results that the medical community continue to ignore. The fact that ozone therapy can be used in different pathologies has been derided by skeptical scientists, who do not know that ozone, as soon as it is dissolved in the water of the plasma, reacts immediately with antioxidants and polyunsaturated fatty acids generating two messengers able to activate blood, endothelial and a variety of parenchyma cells, which, having different functions, are responsible for restoring oxidant homeostasis. The systemic indirect ozone therapy is a safe and effective method to solve the problem of chronic oxidative stress and the related pathologies.